Improving Network Performance of Headquarters and Branches Using Software-Defined Network WAN (SD-WAN) - Muchlisin Muchlisin; Boy Yuliadi (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
The world of information technology is currently developing very quickly, so many private companies are trying to expand their business, especially in the field of information technology. Small to medium companies also need a stable and safe internet network so that the company can grow. Companies that have branch offices in geographically separated locations must use a Wide Area Network (WAN) to be connected. SD-WAN is a special software from Software-Defined Network (SDN) technology, which is used on WAN (wide area network) connections. This research aims to provide solutions to small and medium companies to increase the SLA (Zero Downtime) of their connectivity. Currently, by implementing SD-WAN to improve the performance of head office and branch networks with a low budget. Using the PPDIOO method which is Cisco's life cycle network design approach to support computer network development. The PPDIOO method is an abbreviation of the research design used, namely Prepare, Plan, Design, Implement, Operate and Optimize. After implementing SD-WAN, this becomes a solution that can replace the function of the Juniper router currently used and reduce the burden of internet subscription costs due to its implementation. This SD-WAN simply uses 1 internet link and 1 MPLS link.